Journey on Naphthoquinone and Anthraquinone Derivatives: New Insights in Alzheimer's Disease - Marta Campora; Valeria Francesconi; Silvia Schenone; Bruno Tasso; Michele Tonelli (MDPI AG, 2021)
Alzheimer's disease (AD) is a progressive neurodegenerative disease that is characterized by memory loss, cognitive impairment, and functional decline leading to dementia and death. AD imposes neuronal death by the intricate interplay of different neurochemical factors, which continue to inspire the medicinal chemist as molecular targets for the development of new agents for the treatment of AD with diverse mechanisms of action, but also depict a more complex AD scenario. Within the wide variety of reported molecules, this review summarizes and offers a global overview of recent advancements on naphthoquinone (NQ) and anthraquinone (AQ) derivatives whose more relevant chemical features and structure-activity relationship studies will be discussed with a view to providing the perspective for the design of viable drugs for the treatment of AD. In particular, cholinesterases (ChEs), β-amyloid (Aβ) and tau proteins have been identified as key targets of these classes of compounds, where the NQ or AQ scaffold may contribute to the biological effect against AD as main unit or significant substructure. The multitarget directed ligand (MTDL) strategy will be described, as a chance for these molecules to exhibit significant potential on the road to therapeutics for AD.